DETERMINING ROAD HANDLING ACCORDING TO THE LEVEL OF DAMAGE USING SURFACE DISTRESS INDEX (SDI) METHOD - Paikun, Paikun; Suminar, Elis; Irawan, Aldi; Bahri, Saiful (ASTONJADRO, 2021)
Roads that have been functioned are in good condition, slightly damaged, moderately damaged, and heavily damaged, therefore road maintenance is needed. Road maintenance uses costs, and the available costs are often insufficient to carry out road repairs as a whole, so it is necessary to determine the priority scale of road repairs. The Surface Distress Index (SDI) method is a method used by the DGH to determine the level of road damage, furthermore as a basis for determining the priority scale for road repairs. Along 2.25 km of Jalan Merdeka 1, Sukabumi City, it is the sampling location for the study to determine the condition of road damage. Each investigation point is determined to be 200 m long, starting from the initial STA 0 + 000 - 0 + 200 to the last STA 2 + 200 - 2 + 250. The results showed that the road conditions consisted of moderately damaged, lightly damaged to heavily damaged, so it needed maintenance at STA 0 + 000 - 0 + 400, it needed rehabilitation at STA 0 + 400 - 1 + 800 and STA 2 + 200 - 2 + 250 , as well as need reconstruction at STA 1 + 800 - STA 2 + 200. The results of this study can be used as a basis for determining road handling by policymakers.